UTILIZATION OF ANTENATAL CARE SERVICES AMONG PREGNANT WOMEN AGED (15-49) YEARS IN NORTHERN UGANDA. A CROSS-SECTIONAL STUDY. - Okwany, Jimmy; Nalubega, Jane Frank; semuwemba, Francis (Student’s Journal of Health Research Africa, 2024)
Background. Maternal mortality remains a critical issue globally, particularly affecting low-income developing countries (LDCs). Inadequate utilization of antenatal care (ANC) services, especially in sub-Saharan Africa, is strongly correlated with high maternal mortality ratios. Despite the recognized importance of ANC services in improving maternal and infant health outcomes, studies indicate suboptimal utilization rates. This study aimed to assess the utilization of antenatal care services among pregnant women aged (15-49) years in Northern Uganda. Methodology. This study utilized data from the Uganda Demographic and Health Survey (UDHS) conducted in 2016. A cross-sectional study design was employed, focusing on women aged 15-49 years in Northern Uganda. Quantitative data analysis was conducted using Stata 14, including descriptive and inferential statistics. Factors associated with ANC utilization were assessed through logistic regression analysis, controlling for potential confounders. Results The UDHS 2016 data revealed that 61.72% of women in northern Uganda attended at least four ANC visits, exceeding the global prevalence in high maternal mortality countries. Factors significantly associated with ANC utilization included aged 25-34 years (AOR: 1.28, 95% CI 1.05-1.56, p=0.014), manual occupation (AOR: 1.58, 95% CI 1.17-2.14, p=0.003), women with professional engagement (AOR: 1.43, 95% CI=1.05-1.98), and women with secondary education (AOR: 1.80, 95% CI 1.24-2.6, p=0.002). Conclusion There are promising ANC utilization rates in Northern Uganda but also some key determinants influencing utilization patterns were identified. Recommendation Strategies aimed at improving ANC attendance should consider region-specific interventions targeting factors such as age, occupation, and education of women. Additionally, efforts to promote timely ANC initiation and increase awareness of ANC benefits among women of reproductive age are recommended to further enhance maternal and child health outcomes in Uganda.